High‐dose glucocorticoids for the treatment of ipilimumab‐induced hypophysitis is associated with reduced survival in patients with melanoma. Issue 18 (5th July 2018) - Faje, Alexander T.; Lawrence, Donald; Flaherty, Keith; Freedman, Christine; Fadden, Riley; Rubin, Krista; Cohen, Justine; Sullivan, Ryan J.
Abstract : BACKGROUND: It remains unclear whether high doses of glucocorticoids have a negative impact on the efficacy of checkpoint inhibitors. To control for the potential association between immune‐related adverse events (irAEs) and improved survival, this study examined a unique cohort of patients who had the same irAE treated with varying glucocorticoid doses. METHODS: In total, 98 patients with melanoma who had ipilimumab‐induced hypophysitis were identified retrospectively in the Partners Healthcare system using an automated electronic medical record query tool. Patients with melanoma who received ipilimumab at Massachusetts General Hospital without developing hypophysitis were listed in an actively maintained institutional patient database. Glucocorticoid doses for patients with hypophysitis were categorized as low dose (LD) or high dose (HD). Survival analyses were performed for patients who received ipilimumab monotherapy. RESULTS: Both overall survival (OS) and the time to treatment failure were significantly longer in the LD group compared with the HD group (hazard ratio, 0.24; P  = .002 and 0.28, P  = .001, respectively). Median OS and the time to treatment failure were not reached in the LD group and were 23.3 and 14.5 months, respectively, in the HD group. All patients who had hypophysitis had improved OS compared with patients who did not have hypophysitis (median, 28.2 vs 9.5 months; P  = .0003). This advantage was maintained in the HD group versus the nonhypophysitis group ( P  = .02). Radiologic and endocrinologic outcomes and symptom resolution did not differ in the LD group versus the HD group. CONCLUSIONS: Among patients with melanoma who had ipilimumab‐induced hypophysitis, those who received higher doses of glucocorticoids had reduced survival. This is the first study to demonstrate a potential negative effect of high glucocorticoid doses on the efficacy of checkpoint inhibitors after an irAE. These findings have potential implications for the management of other irAEs. Abstract : This study is the first analysis of the effects of differing glucocorticoid doses on the antitumor efficacy of checkpoint inhibitors after the development of an immune‐related adverse event. The results demonstrate that high dosages of glucocorticoids may have a negative impact on the antitumor efficacy of checkpoint inhibitors and do not improve other outcomes for patients with hypophysitis.